Effect of Two Species of Ticks and Lice on Some Blood and Biochemical Parameters and their Role in the Transmission of Toxoplasma Gondii to Turkey Meleagris Gallopavo during Spring and Summer Seasons in AL-Diwaniyah Province – Iraq - Khalid Thamir Mattar AL-Shaibani (Journal of Global Pharma Technology, 2018)
AL-Diwaniyah governorate was the research place, where the study was conducted in during spring and summer seasons from the start of March 2017 to the end of October 2018. 120 turkey birds were selected from some districts and areas of AL-Diwaniyah governorate such as AL-Diwaniyah, AL-Shamiya, AL-Daghara,AL- Sanniyah, AL-Hamza and Afak, With 20 birds per region (10 per season). Two species of ticks: Argus persicus and Dermacentor variabilis were diagnosed with 15% and 18.3% respectively, and two species of lice: Goniocotes gallinae and Menacanthus straminus with 37.5% and 27.5% sequentially. The results showed a significant increase in the Infection of ticks and lice in spring compared to summer, where the rate of infection of tick and lice was 51.66% and 85%, respectively, while infection rate in summer was 23.33% and 35%, respectively. Infection by lice was high during spring in the areas of AL-Dagara, AL- Saniyah,and AL- Hamza . It was observed that there increasing in the numbers of isolated lice species in these areas in comparison with the number of tick, whereas the lowest rates of infection by ticks and lice were in the province center.  The results revealed a significant decreasing ( P ˂ 0.05 )in the concentration of Hb, the volume of PCV and the total number of RBC of infected birds compared with non-infected, while a high significant increasing was observed in the total number of WBC of infected birds in comparison with non-infected ones. The results of biochemical parameters of serum showed a significant decrease P (0.05) in the values of total protein concentrations, cholesterol and glucose of the infected birds' serum. The lowest values were for infected birds with lice, followed by tick compared to control. Eye examination of the skin and feathers of infected birds illustrated the presence of important changes such as the fall; fracture and lack of feathers completely in some areas of skin as well as wounds, scratches, and bleeding were clearly observed.  The results of polymerase chain reaction (PCR) of tick A. persicus and lice M. stramineus tissues showed that diagnostic gene B1 (399bp) of T.gondii was present in 20 samples of the total number. This indicates the presence of this parasite in its tissues and ability to transmit it.Keywords: Turkey, Tick, Lice, PCR,